Diagnostic and therapeutic management of clinical case of suppurative pre-scapular lymphadenitis in a bull - Abba, Yusuf; Bitrus, Asinamai Athliamai; Abdullah, Faez Firdaus Jesse; Hambali, Idris Umar; Peter, Innocent Damudu; Lim, Eric Teik Chung; Wan Ishak, Wan Mohd Sukri; Mohd Lila, Mohd Azmi (AkiNik Publications, 2018)
A 4 year old Jersey-Friesian cross bull was presented to the Universiti Veterinary hospital, Universiti Putra Malaysia with a ruptured abscess on the right pre-scapular lymph node. The wound was dressed with diluted Hibiscrub® (Chlorhexidine gluconate 4.0%) and povidone iodine. Initial treatment includes Penicillin Streptomycin at 16mg/kg, intramuscularly. Bacterial isolation and sensitivity results revealed the presence of Staphylococcus shleiferi spp shleiferi and Arcanobacterium pyogenes. Both were resistant to gentamycin, penicillin G, sulfazole and streptomycin, but susceptible to tetracycline. The treatment was substituted with oxytetracycline 9mg/kg for 3 days based on the antibiotic susceptibility result. The wound was monitored and observed to have completely healed after 10 days post treatment.